Pharmacological screening of fenofibrate‐loaded solid dispersion in fructose‐induced diabetic rat. (19th April 2020) - Ghosh, Milon Kumar; Wahed, Mir Imam Ibne; Khan, Rafiqul Islam; Habib, Anwar; Barman, Ranjan Kumar
Abstract: Objectives: Hyperlipidaemia is a common phenomenon in diabetes mellitus. Fenofibrate (FF) is a good candidate for the treatment of lipid abnormalities in patients with type 2 diabetes. But the bioavailability as well as therapeutic efficacy of this drug is limited to its dissolution behaviour. Here, the authors assess the therapeutic efficacy of a newly formulated solid dispersion of fenofibrate (SDF) having enhanced dissolution profiles in contrast to pure FF using fructose‐induced diabetic rat model. Methods: Fructose‐induced diabetic rat model was developed to assess the pharmacological efficacy of the formulated SDF, and the results were compared with the effects of conventional FF therapy. Key findings: The 14 days treatment showed better improvement in lipid‐lowering potency of SDF than pure FF. SDF containing one‐third dose of pure FF showed similar effect in terms of triglyceride, total cholesterol and low‐density lipoprotein lowering efficacy, whereas increased high‐density lipoprotein at same extent. The similar dose of SDF produced more prominent effect than FF. Histological studies also demonstrated the enhanced lipid clearance from liver by SDF than FF that was concordant with the biochemical results. Conclusions: This newly formulated SDF would be a promising alternative for conventional fenofibrate in treating hyperlipidaemia.